Mutation analysis of CHCHD10 in different neurodegenerative diseases - Zhang, Ming (2015)
A recent study by Bannwarth et al. (2014) implicated CHCHD10 as a novel gene for amyotrophic lateral sclerosis/frontotemporal lobar degeneration (ALS/FTLD), reporting a p.S59L substitution (c.176C > T; NM_213720.2) in a large French kindred. Affected family members were presented with a complex phenotype that included symptoms of amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration (FTLD), cerebellar ataxia, Parkinson's disease and a mitochondrial myopathy associated with multiple mitochondrial DNA deletions. So far, seven missense CHCHD10 mutations have been reported in patients with a broad phenotypic range, including ALS/FTLD (p.S59L and p.P34S) (Bannwarth et al., 2014; Chaussenot et al., 2014), ALS (p.R15L and p.G66V) (Johnson et al., 2014; Muller et al., 2014), myopathy (p.R15S and p.G58R) (Ajroud-Driss et al., 2015) and late-onset spinal motor neuronopathy (p.G66V) (Penttila et al., 2015). All of them affect exon 2 (a mutational hotspot of CHCHD10).